(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
In this paper,a Mathematica module for singularityfree computations of Euler parameters was established .The basic idea that we follow in developing these computationsis to make the values of the denominators of the fractions used to compute the parameters always maximum, so by this artifice we avoid the divisions by small quantities that causes singularities.